Effect of the thermophysical properties of the material of a local energy source on conditions and characteristics of ignition of metallized composite propellants; Russian Journal of Physical Chemistry B; Vol. 10, iss. 6 - Glushkov D. O. Dmitry Olegovich (2016, 2016)
Title screen